2022
DOI: 10.1371/journal.pone.0271017
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation, water, energy use, and traffic volume affect environmental quality: Go-for-green developmental policies

Abstract: Carbon emissions are primarily the result of human activity in urban areas. Inadequate sanitary facilities, contaminated drinking water, nonrenewable energy, and high traffic congestion have all impacted the natural ecosystem. Using data from 1975 to 2019, the study assessed the impact of the aforementioned variables on Pakistan’s carbon emissions in light of this crucial fact. The ARDL cointegration method was used to estimate the short- and long-run parameter estimates. Urban sanitation challenges and energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 95 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Second, the greater use of energy in industrial production increases the country' economic growth, which helps them utilize natural resources as raw material in industrial production and would enable to obtain foreign reserves for the country. However, the earlier literature shows the concerns of ecological footprints and biowaste, leading the economic growth towards worsening due to compromising healthcare sustainability agenda [60][61][62][63]. In this regard, the study attracted more inbound FDI in cleaner production technologies to offset the adverse effects of industrial pollution, leading to improved economic development.…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
“…Second, the greater use of energy in industrial production increases the country' economic growth, which helps them utilize natural resources as raw material in industrial production and would enable to obtain foreign reserves for the country. However, the earlier literature shows the concerns of ecological footprints and biowaste, leading the economic growth towards worsening due to compromising healthcare sustainability agenda [60][61][62][63]. In this regard, the study attracted more inbound FDI in cleaner production technologies to offset the adverse effects of industrial pollution, leading to improved economic development.…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
“…Thus, it can be concluded that the effect of space utilization, renewable energy utilization, and transportation management simultaneously explains 94.84% of the sustainability of the Mamminasata new city area. Furthermore, the use of renewable energy contributes to economic activities and reduces carbon emissions, especially those produced by human activities Khalil et al, 2022).…”
Section: Control Of Space Utilization and Utilization Of Renewable En...mentioning
confidence: 99%
“…In addition to reducing health costs, increased environmental regulations and investment in sustainable technologies improve environmental quality and improve health outcomes (Omri, Kahouli, Afi, & Kahia, 2022). Considering energy consumption, environmental quality and health expenditure in general the EKC theory provides valuable insights (Khalil et al, 2022). Sustainable development and improving health outcomes can be achieved through environmental regulations (Ameli, Esfandabadi, Sadeghi, Ranjbari, & Zanetti, 2023).…”
Section: Theoretical Foundations For the Relationship Of Variablesmentioning
confidence: 99%